The Christian Ashram Movement in India, 1st edition - Štipl, Zdeněk (Routledge India, 2020)
This book is one of the first to present a definitive history of the Christian Ashram Movement. It offers insights into the development of the Movement, Europe’s Orientalist view of Eastern mysticism and how the concept of the "ashram" spread beyond the borders of India.